Development and optimization of microparticles containing a hypoglycemic fraction of calyces from Physalis peruviana - Sandra Milena Echeverry, Ivonne Helena Valderrama, Geison M. Costa , Luis Fernando Ospina-Giraldo, Diana Marcela Aragón (Journal of Applied Pharmaceutical Science, 2018)
Physalis peruviana L. (Cape gooseberry) is a plant widely cultivated in the Andean mountain in South America and its calyces are the main by-product of the harvest and commercialization of the fruits. Hypoglycemic activity was evaluated to the hydroethanolic extract and its fractions by glucose tolerance test. Since butanolic fraction exhibited hypoglycemic activity as well as the hydroethanolic extract, this fraction was microencapsulated in hypromellose phthalate (HPMCP) by the emulsification-evaporation method. Rutin was the major flavonoid in the whole extract and butanolic fraction. By using Plackett-Burman and Box-Behnken statistical experimental designs, were developed and optimized HPMCP-microparticles loaded with butanolic fraction. Optimized microparticles have an entrapment efficiency of 71% and yield of 64%, only 8% of release at acidic pH and significant hypoglycemic activity. Development and optimization of microencapsulated butanolic fraction of calyces from P. peruviana is an important contribution to improve its hypoglycemic activity as a promising therapeutic strategy.
Keywords: Hypoglycemic activity, microparticles, Physalis peruviana calyces, rutin.